Fire stimulates grass flowering in the Cerrado independent of season - Fidelis, Alessandra [UNESP]; Zirondi, Heloiza L. [UNESP]; Rossatto, Davi R. [UNESP]; Zanzarini, Vagner [UNESP] (Wiley, 2022)
Questions: Post-fire flowering is an underestimated plant trait of many fire-prone ecosystems and is rarely considered for tropical savannas. Therefore, we analyzed the effects of fire season and history on post-fire flowering of grass species in a tropical savanna (Cerrado), by evaluating the number of species, frequency of individuals and number of reproductive tillers after wet- and dry-season fires, and under different fire histories. Locations: Open savannas (campo sujo) of the Cerrado in central Brazil (Reserva Natural Serra do Tombador [RNST], 13°35–13°38′ S, 47°45′–47°51′ W). Methods: We sampled flowering individuals in 10 Poaceae species and counted flowering/vegetative tillers of grass species in 1 m × 1 m plots after wet- and dry-season fires and under different fire histories (3, 18 and 72 months post fire). Results: Some of the studied species responded differently to fire according to season but most flowered after fire events. Moreover, the exclusion of fire led to a decrease in the number of flowering individuals and reproductive tillers of grass species. Conclusions: We describe a unique event for tropical savannas: beside rapid resprout after fire events, grasses can allocate resources for both vegetative and reproductive tiller production, even during the dry season. If fire is excluded from the system, fewer grass species and individuals will flower and there will be a lower percentage of reproductive tillers, showing the importance of fire for grass flowering in these tropical savannas, independently of fire season.
Keywords: C4 grasses; fire-stimulated flowering; grasses; tropical savannas; wet and dry season